Exploring Educational Management Through Inductive Analysis : Addressing Fallacies in Qualitative Research Methodologies - Nuriman, Nuriman; Yusnaini; Setiawan (ABANNA: Journal Of Contemporary Islamic Education, 2024)
This research investigates the challenges faced by students in completing academic reports, particularly in anthropology, sociology, and education. Despite the growing importance of quality academic writing, students often struggle with proper documentation, leading to incomplete or inaccurate reports. A key gap identified is the lack of a systematic approach to understanding these issues, especially in the context of methodological challenges in academic reporting. The study employs a qualitative method with an inductive approach, utilizing documentation techniques and content analysis. Data was collected from various sources, including published and unpublished academic documents such as theses, dissertations, research papers, and books. Triangulation through peer discussions and document analysis ensured the reliability and validity of the findings. The research identifies common issues in academic reporting, including difficulties in structuring research and presenting findings clearly. It also highlights the role of proper documentation in enhancing the quality of academic work. The study recommends that academic institutions implement structured writing workshops and emphasize proper documentation techniques. Additionally, students should be trained in effective research methodologies and document handling. This research has significant implications for improving academic writing practices and methodologies in higher education, ultimately enhancing the quality of scholarly work.